Multimodal Metaphors of Interculturereality / Metaforas multimodais da interculturealidade (Revista de Estudos da Linguagem, 2020)
Abstract: The present paper looks at the interactive construction of multimodal metaphors of interculturereality – a term coined by the author from interculturality and intercorporeality, assuming that intercultural interaction is always an embodied phenomenon, shared among its participants. For this, two videotaped sequences of a group conversation are analyzed drawing upon interaction analysis (Couper-Kuhlen; Selting, 2018). The data was transcribed following the GAT2 (Selting et al., 2011) guidelines, including gesture form annotation, which relied on the system described by Bressem (2013). Gesture function was interpreted drawing on the interactional context and on the system proposed by Kendon (2004) and Bressem and Müller (2013). The results question the validity of the classical conduit metaphor of communication (Reddy, 1979) in the intercultural context and instead propose an embodied approach to the conceptualization of the understanding process among the participants. The analysis also shows that even though the metaphors are multimodal, the metaphoric content is not always evenly distributed among the different modalities (speech, gesture). Apart from that, the metaphorical content is constructed sequentially, referring to preceding metaphors used by the same or different interlocutors and associated with metaphorical blends.Keywords: metaphors; multimodality; interculturality; intercorporeality; migration.Resumo: O presente artigo analisa a construção interativa de metáforas multimodais da interculturealidade – um termo proveniente da interculturalidade e intercorporealidade, assumindo que a interação intercultural é sempre um fenômeno incorporado, compartilhado entre os seus participantes. Para tal, duas sequências gravadas em vídeo de uma conversa em grupo serão analisadas com base na análise da interação (COUPER-KUHLEN; SELTING, 2018). Os dados foram transcritos seguindo as orientações do sistema GAT2 (SELTING et al., 2011), incluindo a anotação da forma gestual, que se baseou no sistema descrito por Bressem (2013). A função dos gestos foi interpretada com base no contexto interacional e no sistema proposto por Kendon (2004) e Bressem e Müller (2013). Os resultados questionam a validade da metáfora clássica do conduto de comunicação (REDDY, 2012) no contexto intercultural e, além disso, propõem uma abordagem corporificada da conceituação do processo de entendimento entre os participantes. A análise também mostra que, embora as metáforas sejam multimodais, o conteúdo metafórico não é sempre uniformemente distribuído entre as diferentes modalidades (fala, gesto). Além disso, o conteúdo metafórico é construído sequencialmente, referindo-se a metáforas anteriores utilizadas pelos mesmos ou diferentes interlocutores e recorrendo a mesclagens metafóricas.Palavras-chave: metáforas; multimodalidade; interculturalidade; intercorporealidade; migração.